2022
DOI: 10.3389/fenvs.2022.992559
|View full text |Cite
|
Sign up to set email alerts
|

ESG performance, investors’ heterogeneous beliefs, and cost of equity capital in China

Abstract: Previous studies on the relationship between environmental, social and governance (ESG) information disclosure and cost of equity (COE) have found mixed results. They conclude that this relationship may be affected by some attributes of the company inside. In this study, we examine whether investors’heterogeneous beliefs moderates the relationship between ESG performance and COE. Our sample starts with ESG-rating firms included in Huazheng index of the Wind China financial database (WIND) for years 2015–2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As in research methodology adopted by Tang [57], the ESG rating and its segmented ratings constructed by the mainstream domestic ESG rating agency Huazheng Index Information Service and obtained from the Information Financial Terminal of Wind are used in this study to measure the ESG of the enterprise and are logarithmically processed. The ESG evaluation system of the Huazheng Index Information Service draws on overseas ESG development experience and is also adapted to China's current situation.…”
Section: Esgmentioning
confidence: 99%
“…As in research methodology adopted by Tang [57], the ESG rating and its segmented ratings constructed by the mainstream domestic ESG rating agency Huazheng Index Information Service and obtained from the Information Financial Terminal of Wind are used in this study to measure the ESG of the enterprise and are logarithmically processed. The ESG evaluation system of the Huazheng Index Information Service draws on overseas ESG development experience and is also adapted to China's current situation.…”
Section: Esgmentioning
confidence: 99%
“…Secondly, corporate ESG performance can reduce the cost of debt financing and equity financing by reducing the information asymmetry with creditors and equity holders. Raimo et al (2021) [3] and Tang (2022) [4] found that the higher the transparency of ESG information disclosure, the lower the cost of debt financing. Finally, corporate ESG performance can comprehensively improve financial performance and market value by easing financing constraints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With developing, ESG is increasingly valued by enterprises. Tang [14] believes that enterprises with better ESG performance can not only reduce the cost of debt financing, but also alleviate investors' expected risks, thereby reducing the cost of equity capital.…”
Section: Introductionmentioning
confidence: 99%